Overcoming protein-energy malnutrition in older adults in the residential care setting: A narrative review of causes and interventions - Mathewson, Sophie L.; Azevedo, Paula S. [UNESP]; Gordon, Adam L.; Phillips, Bethan E.; Greig, Carolyn A. (Elsevier, 2021)
Malnutrition, in particular protein-energy malnutrition, is a highly prevalent condition in older adults, and is associated with low muscle mass and function, and increased prevalence of physical frailty. Malnutrition is often exacerbated in the residential care setting due to factors including lack of dentition and appetite, and increased prevalence of dementia and dysphagia. This review aims to provide an overview of the available literature in older adults in the residential care setting regarding the following: links between sarcopenia, frailty, and malnutrition (in particular, protein-energy malnutrition (PEM)), recognition and diagnosis of malnutrition, factors contributing to PEM, and the effectiveness of different forms of protein supplementation (in particular, oral nutritional supplementation (ONS) and protein-fortified foods (PFF)) to target PEM. This review found a lack of consensus on effective malnutrition diagnostic tools and lack of universal requirement for malnutrition screening in the residential care setting, making identifying and treating malnutrition in this population a challenge. When assessing the use of protein supplementation in the residential care setting, the two primary forms of supplementation were ONS and PFF. There is evidence that ONS and PFF increase protein and energy intakes in residential care setting, yet compliance with supplementation and their impact on functional status is unclear and conflicting. Further research comparing the use of ONS and PFF is needed to fully determine feasibility and efficacy of protein supplementation in the residential care setting.
Keywords: Frailty; Protein-energy malnutrition; Residential care setting; Sarcopenia; Supplementation